Conservation Status of Philippine Fruit Bats (Pteropodidae) - Utzurrum, Ruth C. B. (Silliman Journal, 2024)
Of the 25 species of fruit bats presently known from the Philippines, 15 (60%) are endemic. The conservation status of each species is reviewed based on published and unpublished results of studies conducted in the last ten years. Of the 15 endemic species two, Acerodon lucifer and Dobsonia chapmani are now considered extinct. Species recognized to be most highly endangered are Acerodon jubatus, A, leucotis, Eonycteris robusta, Nyctimene rabori and Pteropus leucopterus. These five species are part of the endemic fauna. Factors considered to contribute to population declines are discussed, including habitat destruction and geographical distribution. The discussion focuses on strategies for conservation.